The Formation of Massive Stars: from Herschel to Near-Infrared - Paolo Persi; Mauricio Tapia (Acta Polytechnica CTU Proceedings)
We have studied a number of selected high mass star forming regions, including high resolution near-infrared broad- and narrow-band imaging, Herschel (70, 160, 250, 350 and 500 μm) and Spitzer (3.6, 4.5, 5.8 and 8.0 m) images. The preliminary results of one of this region, IRAS 19388+2357(MOL110) are discussed. In this region a dense core has been detected in the far-infrared, and a young stellar cluster has been found around this core. Combining near-IR data with Spitzer and Herschel photometry we have derived the spectral energy distribution of Mol110. Finally comparing our H2 and Kc narrow-band images, we have found an H2 jet in this region.